O slovarskem prikazu slovenske vezljivosti - Žele, Andreja (Jezik in slovstvo, 2001)
The article discusses the theoretical foundations of valency that have to be applied in designing a dictionary of valency in the Slovene language. Practical examples are provided of how treatment of valency in a dictionary could be further improved.
Keywords: Slovene; slovenščina; leksikografija; lexicography; vezljivost; verb; glagol; samostalnik; pridevnik